The faith of scientists in their own words - Frankenberry, Nancy, 1947- (Princeton University Press, 2008)
The Faith of Scientists is an anthology of writings by twenty-one legendary scientists, from the dawn of the Scientific Revolution to the frontiers of science today, about their faith, their views about God, and the place religion holds--or doesn't--in their lives in light of their commitment to science. --From publisher description.